(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
The current study was conducted in the laboratories of the Plant Protection Department/College of Agriculture and Forestry/University of Mosul during the year 2019-2020. The aim of this study was to evaluate the efficiency of the Iraqi isolate of the biological control fungi Beauveria bassian and Metarhizium anisopliaeas chemical pesticides alternatives in controlling different stages of the greater wax moth Galleria mellonella. The results of the biological effect of the fungi Beauveria bassiana and Metarhizium anisopliae on the greater wax moth life stages showed that the cumulative mortality of eggs increased gradually with increasing concentration used. However, Beauveria bassiana was more efficient in achieving higher mortality rates than M. anisopliae in general. The highest cumulative mortality rate for eggs was at the highest concentration (7.5g/l) for both fungi. On the other hand, it was found that the highest mortality rate in wax moth larvae was inB. bassianacombined treatmentwhere spraying the larvae and the feed. The third and fourth larval instars were more sensitive than the sixth and seventh larval instars, which were not affected by the lower concentrations of the pesticide (2.5 and 5 g/L), regardless of pesticide type. The results also showed that the mortality rate in all phases increases with the increase in the post-treatment period. The results of the study indicated the superiority of B. bassiana in all treatments, concentrations and periods after treatment and led to the highest mortality rate compared with using M. anisopliae. The cumulative mortality rate in the greater wax moth was directly proportional to the increase in treatment methods and the increase in concentration and the time period after treatment.